Home- or Institutional Hemodialysis? - a Matched Pair-Cohort Study Comparing Survival and Some Modifiable Factors Related to Survival - Helena Rydell; Naomi Clyne; Mårten Segelmark (Karger Publishers, 2016)
Background/Aims: Survival for dialysis patients is poor. Earlier studies have shown better survival in home-hemodialysis (HHD). The aims of this study are to compare survival for matched patients with HHD and institutional hemodialysis (IHD) and to elucidate the effect on factors related to survival such as hyperphosphatemia, fluid overload and anemia. Methods: In this retrospective, observational study, incident patients starting HHD and IHD were matched according to sex, age, comorbidity and date of start. Survival analysis was performed both as "intention to treat" including renal transplantation and "on treatment" with censoring at the date of transplantation. Dialysis doses, laboratory parameters and prescriptions of medications were compared. Results: After matching, 41 pairs of patients, with HHD and IHD, were included. Survival among HHD patients was longer compared with IHD, median survival being 17.3 and 13.0 years (p=0.016), respectively. The "on treatment" analysis, also favoured HHD (p=0.015). HHD patients had lower phosphate, 1.5 mmol/L compared with 2.1 mmol/L (pConclusion: HHD shows better survival compared with IHD, also after controlling for patient selection. This could be caused by better phosphate and/or fluid balance associated with higher dialysis doses.